1998
DOI: 10.1080/095530098141339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 50 Hz magnetic field on cognitive function in humans

Abstract: These tests indicated at least temporary deterioration in attention, and working and secondary memory performance while a 50 Hz field is applied. There were no adverse effects on speed from any of the tasks. It was not possible in this study to be sure if these effects were persistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…We investigated the effects of UMTS-like radiation on brain functioning with the Simple Reaction Time Task (SRT) and Two-Choice Reaction Time Task (CRT) ( Koivisto et al 2000b ; Preece et al 1998 , 1999 ), the N-back Task (N-back) ( Koivisto et al 2000a ), and the Visual Selective Attention Task (VSAT) adapted from Zwamborn et al (2003) and applied the tasks in fixed order (SRT, CRT, 1-, 2-, 3-back, VSAT). We implemented the tasks using software from e-Prime (Psychology Software Tools Inc., Pittsburgh, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the effects of UMTS-like radiation on brain functioning with the Simple Reaction Time Task (SRT) and Two-Choice Reaction Time Task (CRT) ( Koivisto et al 2000b ; Preece et al 1998 , 1999 ), the N-back Task (N-back) ( Koivisto et al 2000a ), and the Visual Selective Attention Task (VSAT) adapted from Zwamborn et al (2003) and applied the tasks in fixed order (SRT, CRT, 1-, 2-, 3-back, VSAT). We implemented the tasks using software from e-Prime (Psychology Software Tools Inc., Pittsburgh, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that ELM exposure impaired acquisition and consolidation of spatial memory in rodents [4][6] and produced deficits in detour learning and one-trial passive avoidance learning in chicks [7], [8]. Moreover, it has been reported that exposure to ELM impaired the performance of humans in word recognition and visual discrimination tasks [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI studies have identified the activation of a network of brain regions involved in this task, which include the cerebellum, the premotor cortex and the superior parietal lobule [ 36 38 ]. Interestingly, one study investigating the effect of a 600 μT, 50 Hz MF in humans found out a decreased performance in attentional and memory tasks [ 39 ]. More recently, Corbacio et al [ 25 ] reported that the improvement associated with the repetition of a short term memory task no longer existed after a one-hour exposure to a 3 mT, 60 Hz MF.…”
Section: Introductionmentioning
confidence: 99%